Effects of fenofibrate therapy on renal function in primary gout patients. (11th March 2021) - Li, Xinde; Sun, Wenyan; Lu, Jie; He, Yuwei; Chen, Ying; Ren, Wei; Cui, Lingling; Liu, Zhen; Wang, Can; Wang, Xuefeng; Ma, Lidan; Cheng, Xiaoyu; et al.
Abstract: Objective: To investigate the incidence and potential risk factors for development of fenofibrate-associated nephrotoxicity in gout patients. Methods: A total of 983 gout patients on fenofibrate treatment who visited the dedicated Gout Clinic at the Affiliated Hospital of Qingdao University between September 2016 and June 2020 were retrospectively enrolled from the electronic records system. Fenofibrate-associated nephrotoxicity was defined as an increase in serum creatinine (SCr) ≥0.3 mg/dl within 6 months of fenofibrate initiation. The change trend of SCr and uric acid levels during the treatment period were assessed by a generalised additive mixed model (GAMM). Multivariate analysis was performed for risk factors affecting elevated SCr. Results: A total of 100 (10.2%) patients experienced an increase in SCr ≥0.3 mg/dl within 6 months after fenofibrate initiation. The median change of SCr in the whole cohort was 0.11 mg/dl [interquartile range (IQR) 0.03–0.20], whereas it was 0.36 (0.33–0.45) in the fenofibrate-associated nephrotoxicity group. In a multivariable regression model, chronic kidney disease (CKD) [odds ratio (OR) 2.39 (95% CI 1.48, 3.86)] and tophus [OR 2.29 (95% CI 1.39, 3.78)] were identified to be risk predictors, independent of measured covariates, of fenofibrate-associated nephrotoxicity. During the treatment period, although SCr temporarily increased, serum urate and triglyceride concentrations decreased using the interaction analysis of GAMM. Of those with fenofibrate withdrawal records, the SCr increase in 65% of patients was reversed after an average of 49 days off the drug. Conclusions: This observational study implied that fenofibrate-associated nephrotoxicity occurs frequently in gout patients, especially in patients with tophi or CKD. The potential renal risks of fenofibrate usage in gout needs additional research.